Policing performance management systems: Identifying key design elements within a `new' public management context - Gillespie, John (2006)
The new public management (NPM) philosophy and move towards a governance approach places emphasis on the accountability of individuals, supervisors and managers relative to practice, processes and designated outcome - conformance and performance. A dichotomy is highlighted working within the NPM environment where managers need to practice creative and innovative freedoms, and at the same time to exercise constraint and compliance within a regulated and permission seeking framework. This situation can create inertia in respect to performance reforms within the public service. Police Services in Australia, and in particular the Western Australia Police (WAPOL) have made some inroads into providing a foundation for a performance management (PM) approach. However, despite two decades performance management system (PMS) design, relevancy and application within the WA environment is not attuned to the internal and external requirements. This misalignment has led to limited understanding and successful application amongst policing frontline manager